Enhancing the Self-Reliance of Smallholder Sheep Farmers via Educational Interventions on Silage Feed Processing in Songgon District, Banyuwangi: Peningkatan Kemandirian Peternak Domba Rakyat Melalui Edukasi Pengolahan Pakan Silase di Kecamatan Songgon, Banyuwangi - dwi priyadi; Ninik Sri Rahayu; Harvey Febrianta (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Smallholder sheep farmers play a pivotal role in meeting the national demand for animal protein. Enhancing farmers’ capacity in modern feed processing methods directly contributes to improving both the quality and quantity of sheep production. This study introduces the concept of a livelihood-improvement economy model through the implementation of silage fermentation techniques within farmer groups in Sumberarum Village, Songgon District, Banyuwangi. A structured questionnaire was administered to assess farmers’ understanding of silage processing and to collect demographic data. Subsequently, knowledge transfer activities were conducted and evaluated using pre- and post-test analysis with the Wilcoxon Signed Ranks Test. To date, no prior studies have examined the introduction of silage feed among smallholder farmers in Songgon District. The demographic profile of the farmer group was predominantly composed of junior high school graduates (53.3%), with the majority engaged in farming and livestock rearing as their primary occupation (66.7%). Most respondents were aged between 31–40 years (40%). Initial knowledge regarding silage production and the use of processing equipment was extremely limited (0%). The knowledge transfer process was successfully implemented, as evidenced by a significant improvement in farmers’ understanding based on the Wilcoxon test results. The adoption of silage has proven to facilitate sheep management practices and is highly compatible with the local characteristics of Sumberarum Village, where forest fodder is abundantly available as a free raw material for silage production.